The Kake Climate Partnership: Implementing a knowledge co-production framework to provide climate services in Southeast Alaska - Figus, Elizabeth; Ki'yee Jackson, Burt; Trainor, Sarah F. (Frontiers in Climate, 2022)
This paper provides a case study analysis of knowledge co-production with an Indigenous community and Tribe in Southeast Alaska that has provided climate services and information in support of climate adaptation and mitigation with community identified priorities of food sovereignty and food security. Our objectives are to (1) describe an application of a theoretical framework that is specific to co-production among Indigenous and non-Indigenous partners, and (2) reflect on the ways in which this application supports relevance and use of climate services in an Indigenous community. Methods included text analysis of written research logs, review of monthly project briefings and structured discussions among a diverse author team. We found that co-production can be used to explicitly define a collective vision among partners that is a transformative way of doing applied climate and environmental science. As such, the role of the university researcher shifted from focusing on personal research interests to a focus on supporting local needs and priorities. When the climate services process is centered on Tribal and community priorities and locally identified science needs, the climate science aspect becomes just one element in the implementation of a larger local vision and goals. Challenges our team encountered during the study were related to logistics, communication, juggling priorities of multiple partners, capacity, and conducting community-based research during a global pandemic. We recommend that future efforts to co-produce climate services through research, adaptation planning, and mitigation be institutionalized and maintained over decadal, not annual, timescales.